Characterization, optical properties and laser ablation behavior of epoxy resin coatings reinforced with high reflectivity ceramic particles. (11th April 2018) - Li, Wenzhi; Kong, Jing; Wu, Taotao; Gao, Lihong; Ma, Zhuang; Liu, Yanbo; Wang, Fuchi; Wei, Chenghua; Wang, Lijun
Abstract: Thermal damage induced by high power energy, especially high power laser, significantly affects the lifetime and performance of equipment. High-reflectance coating/film has attracted considerable attention due to its good performance in the damage protection. Preparing a high-reflectance coating with high reaction endothermal enthalpy will effectively consume a large amount of incident energy and in turn protect the substrate from thermal damage. In this study, a low temperature process was used to prepare coatings onto substrate with complex shape and avoid thermal effect during molding. An advanced high reflection ceramic powder, La1−x Srx TiO3+ δ, was added in the epoxy adhesive matrix to improve the reflectivity of coating. The optical properties and laser ablation behaviors of coatings with different ceramic additive ratio of La1−x Srx TiO3+ δ and modified epoxy-La1−x Srx TiO3+ δ with ammonium polyphosphate coatings were investigated, respectively. We found that the reflectivity of coatings is extremely high due to mixed high-reflection La1−x Srx TiO3+ δ particles, up to 96% at 1070 nm, which can significantly improve the laser resistance. In addition, the ammonium polyphosphate modifies the residual carbon structure of epoxy resin from discontinuous fine particles structure to continuous and porous structure, which greatly enhances the thermal-insulation property of coating. Furthermore, the laser ablation threshold is improved obviously, which is from 800 W cm −2 to 1000 W cm −2 .